2015
DOI: 10.1002/iid3.67
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of CD200R3 on mouse basophils as a novel marker for IgG1‐mediated anaphylaxis

Abstract: IgE-mediated mast cell activation is the trigger of anaphylaxis in humans, whereas it is known that not only IgE but also IgG can induce anaphylaxis in mice. In our preliminary experiments, the expression of a murine basophil identification marker, CD200R3, on antigen-sensitized basophils decreased following specific antigen challenge. Interestingly, this decrease did not always correspond with increased expression of the IgE-mediated basophil activation marker CD200R1. Since IgG as well as IgE plays a role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
(60 reference statements)
2
15
0
Order By: Relevance
“…Basophils are known to be pivotal for IgG-induced anaphylaxis, 38 and the basophilic surface receptor CD200R3 has recently been demonstrated to be a marker for anti-FcgR antibody-mediated anaphylaxis. 13,38 We confirmed the finding that the 2.4G2-mediated anaphylactic response significantly lowered CD200R3 levels on basophils, an effect absent in response to 2.4G2 scFv-MSA treatment. In addition to the decreased CD200R3 level, we observed a transient basophil depletion in response to 2.4G2 treatment, but not 2.4G2 scFv-MSA.…”
supporting
confidence: 84%
See 4 more Smart Citations
“…Basophils are known to be pivotal for IgG-induced anaphylaxis, 38 and the basophilic surface receptor CD200R3 has recently been demonstrated to be a marker for anti-FcgR antibody-mediated anaphylaxis. 13,38 We confirmed the finding that the 2.4G2-mediated anaphylactic response significantly lowered CD200R3 levels on basophils, an effect absent in response to 2.4G2 scFv-MSA treatment. In addition to the decreased CD200R3 level, we observed a transient basophil depletion in response to 2.4G2 treatment, but not 2.4G2 scFv-MSA.…”
supporting
confidence: 84%
“…A recent report demonstrated that 2.4G2-induced anaphylaxis significantly reduced basophil expression of CD200R3, an activating cell surface receptor. 13 CD200R3 was expressed on basophils ( Figure 5A-B). The administration of 0.43 nmol (65 mg) 2.4G2 rapidly reduced the ability to detect CD200R3 on basophils, which partially recovered after 24 hours ( Figure 5C).…”
Section: 4g2 Scfv-msa Inhibits Fcgriii-but Not Fcgriv-mediated Itpmentioning
confidence: 99%
See 3 more Smart Citations